2020
DOI: 10.1002/cac2.12109
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of long noncoding RNAs in cholangiocarcinoma: Advances and challenges

Abstract: Cholangiocarcinoma (CCA), a cancer with a relatively low incidence rate, is usually associated with poor prognosis. Current modalities for the diagnosis and treatment of CCA patients are still far from satisfactory. In recent years, numerous long noncoding RNAs (lncRNAs) have been identified as crucial players in the development of various cancers, including CCA. Abnormally expressed lncRNAs in CCA, regulated by some upstream molecules, significantly influence the biological behavior of tumor cells and are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 173 publications
0
12
0
Order By: Relevance
“…Due to its unclear molecular mechanisms, current clinical diagnosis and treatment for CCA remain unsatisfactory. A large body of recent research has shown that lncRNAs play critical roles in the occurrence and development of various types of cancer [10,11], including CCA [12]. lncRNAs have been implicated in the splicing, export and translation of mRNAs and regulate the stability and post-translational modification of target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its unclear molecular mechanisms, current clinical diagnosis and treatment for CCA remain unsatisfactory. A large body of recent research has shown that lncRNAs play critical roles in the occurrence and development of various types of cancer [10,11], including CCA [12]. lncRNAs have been implicated in the splicing, export and translation of mRNAs and regulate the stability and post-translational modification of target proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Competing endogenous RNA is an important mechanism for lncRNA to regulate cancer progression and chemoresistance. 29,30 To better understand the regulation mechanism of genes on chemoresistance, a ceRNA axis (SVIL-AS1/miR-103a/ICE1) was constructed based on the key chemotherapyrelated module. Kaplan-Meier survival analysis of genes in SVIL-AS1/miR-103a/ICE1 axis showed that in the LUAD patients receiving chemotherapy, high expression of SVIL-AS1 and ICE1 corresponded to a better prognosis, while high expression of miR-103a corresponded to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its insidious onset, CCA is also characterized by high malignancy and early recurrence [23][24][25]28] . Studies have reported that lncRNAs are crucial regulators of diverse biological processes of mRNA and play essential roles in tumorigenesis [29][30][31][32] . Therefore, in this study, we aimed at identifying prognostic-related DElncRNAs in CCA and validated their effects on CCA tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%